A Model of Rush-Hour Traffic in an Isotropic Downtown Area - Richard J. Arnott; Anatolii Kokoza; Mehdi Naji (Center for Economic Studies and ifo Institute (CESifo), 2015)
For a quarter century, a top priority in transportation economic theory has been to develop models of rush-hour traffic dynamics that incorporate traffic jams (hypercongestion). The difficulty has been that “proper” models result in mathematical intractabilty, while none of the proposed approximating models has gained general acceptance. This paper takes a different tack, focusing on a particular proper model in which commuters decide when to travel so as to minimize a trip cost function that is linear in travel time and schedule delay (the so-called á-â-\~a variant of the bottleneck model). Solutions of all the model variants entail departure/arrival masses.
Keywords: L91; R41; 330; equilibrium; rush hour; traffic congestion